Non-host plant odors influence the tritrophic interaction between tomato, its foliar herbivore Tuta absoluta and mirid predator Nesidiocoris tenuis - Adams, Bashiru; Yusuf, Abdullahi Ahmed; Torto, Baldwyn; Khamis, Fathiya Mbarak (Frontiers in Plant Science, 2023)
The tomato leafminer, Tuta absoluta (Meyrick) is a destructive invasive pest of cultivated tomato (Solanum lycopersicum L.) and other Solanaceae plants, with yield losses of 80-100%. Mirid predators are key natural enemies of T. absoluta, but they also feed on host plants in the absence of their prey. Management of T. absoluta is a challenge due to its high biotic potential, resistance to many insecticides and the absence of sufficiently adapted auxiliary fauna in its new dispersion zones. Olfaction plays an important role in the tritrophic interaction between the host plant tomato, its herbivore pest T. absoluta and its mirid predators, which can be influenced by non-host plant odours. However, how non-host odours shape this interaction is poorly understood. Previously, we had demonstrated the belowground crop protection properties of certain Asteraceae plants against the root-knot nematode Meloidogyne incognita, pest of tomato and other Solanaceae plants. Additionally, Asteraceae plants impact negatively on the feeding behaviour of above-ground pests of Solanaceae plants, including the greenhouse whitefly and green peach aphid. Here, we tested the hypothesis that foliar volatiles from some of these non-host Asteraceae plants can influence the tomato-T. absoluta-mirid predator tritrophic interaction. In olfactometer assays, T. absoluta females were attracted to volatiles of the Solanaceae host plants tomato and giant nightshade (Solanum scabrum) but avoided volatiles of the Asteraceae plants, blackjack (Bidens pilosa) and marigold (Tagetes minuta), and the positive control, wild tomato (Lycopersicon esculentum var. cerasiforme) (Solanaceae), when tested alone or in combination with the host plants. Coupled gas chromatography-mass spectrometry analysis showed that host and non-host plants varied in their emission of volatiles, mainly monoterpenes and sesquiterpenes. Random forest analysis combined with behavioural assays identified monoterpenes as the host plant attractive blend to T. absoluta and its mirid predator, with sesquiterpenes identified as the non-host plant repellent blend against T. absoluta. Contrastingly, the mirid predator was indifferent to the non-host plant repellent sesquiterpenes. Our findings indicate that terpenes influence the tomato-T. absoluta-mirid predator tritrophic interaction. Further, our results emphasise the importance of studying crop protection from a holistic approach to identify companion crops that serve multi-functional roles.